'Things were good during Tito's times, my parents say': How young Croatian generations negotiated the socially mediated frames of the recent Yugoslav past. (December 2020) - Vuckovic Juros, Tanja
How do new generations in a society negotiate different perspectives of a controversial past available from various sources? How do they use the past to make sense of their lives? Using in-depth interviews with 72 young members of the first two Croatian post-Yugoslav generations, this study analysed how these young people acquired elements of their repertoires on the recent Yugoslav past from family members, school and the media, how they assessed these elements in terms of plausibility and legitimacy, and how they appropriated or questioned them. The study's findings suggest that the credibility of the socially mediated perspectives of the past was increased by the emotional bond with the sources who adopted the role of witnesses, and by the fit with the personal concerns of the meaning-making audience. As a result, the most successful were the frames transmitted by the communicative sources through social interaction, rather than by the institutionalized sources.